1996
DOI: 10.1111/j.1365-2044.1996.tb07782.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid aspiration prophylaxis for emergency Caesarean section

Abstract: . After pooling the data, median (range) gastric volume in groups C and M C (55(0-360) mi) was greater than in groups ml, p c 0.05). Median (range)pH was lower in groups C and M C (4.97t0.766.99)) than in groups OC, RC,, p c 0.001). The proportion of patients with pH < 3.5 and volume >25ml in the C and MC groups (431 185) was greater than that in the OC, RC, OMC and RMC groups (1 8/ 199, p < 0.001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…A 0.3 mol/l (8.8%) in a volume of 30 ml has pH of 8.4 and causes mean pH to increase to more than 6 for one hour. Molar solution of sodium citrate has been found to be equally effective in emergency and elective cases and with either general or regional anesthesia (Lin et al 1996, Stuart et al 1996. A rebound decrease in gastric pH below 2.5 can occur therefore sodium citrate 0.3 mol/l is recommended as a regular 2-4 hourly regimen for women in labor (Robert & Shirley, 1976).…”
Section: Sodium Citratementioning
confidence: 99%
See 2 more Smart Citations
“…A 0.3 mol/l (8.8%) in a volume of 30 ml has pH of 8.4 and causes mean pH to increase to more than 6 for one hour. Molar solution of sodium citrate has been found to be equally effective in emergency and elective cases and with either general or regional anesthesia (Lin et al 1996, Stuart et al 1996. A rebound decrease in gastric pH below 2.5 can occur therefore sodium citrate 0.3 mol/l is recommended as a regular 2-4 hourly regimen for women in labor (Robert & Shirley, 1976).…”
Section: Sodium Citratementioning
confidence: 99%
“…Metoclopramide, the most frequently used increases the rate of gastric emptying, has an antiemetic and increases lower esophageal sphincter tone. It has been shown that in combination with other agents in obstetric patients at a dose of 10 mg intravenous (Stuart et al 1996) …”
Section: Prokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other interventions to reduce gastric contents volume and ⁄ or increase pH might intuitively reduce the risk and severity of pulmonary aspiration, including pre-surgery gastric tube drainage, use of postpyloric feeding tubes and use of pro-kinetic therapy, although evidence is limited and extrapolated from other populations e.g. elective surgery, critical care or obstetrics [30][31][32][33][34]. The presence of a tracheal tube cannot guarantee airway protection and in cases of intestinal obstruction, intra-operative enterostomy and drainage may be preferable to 'milking back' large volumes of fluid that may bypass a nasogastric tube.…”
Section: Management and Protection Of The Airway Including Pulmonary mentioning
confidence: 99%
“…Neutrophils are the primary mediators of lung injury following aspiration of gastric contents [14, 15]. Although risk factors for acid aspiration continue to be debated, the literature suggests that patients with a gastric pH of <2.5 and a gastric volume of at least 25 ml are at greatest risk [16]. …”
Section: Conditions Requiring Inpatient Antisecretory Therapymentioning
confidence: 99%